Tartaglia's science of weights and mechanics in the sixteenth century : selections from Quesiti et inventioni diverse: books VII-VIII /: selections from Quesiti et inventioni diverse: books VII-VIII. (2016) - Pisano, Raffaele, 1970-; Capecchi, Danilo
No abstract available